Unraveling the causes of sarcopenia: Roles of neuromuscular junction impairment and mitochondrial dysfunction - Yanmei Miao; Leiyu Xie; Jiamei Song; Xing Cai; Jinghe Yang; Xinglong Ma; Shaolin Chen; Peng Xie (2024)
Abstract Sarcopenia is a systemic skeletal muscle disease characterized by a decline in skeletal muscle mass and function. Originally defined as an age‐associated condition, sarcopenia presently also encompasses muscular atrophy due to various pathological factors, such as intensive care unit‐acquired weakness, inactivity, and malnutrition. The exact pathogenesis of sarcopenia is still unknown; herein, we review the pathological roles of the neuromuscular junction and mitochondria in this condition. Sarcopenia is caused by complex and interdependent pathophysiological mechanisms, including aging, neuromuscular junction impairment, mitochondrial dysfunction, insulin resistance, lipotoxicity, endocrine factors, oxidative stress, and inflammation. Among these, neuromuscular junction instability and mitochondrial dysfunction are particularly significant. Dysfunction in neuromuscular junction can lead to muscle weakness or paralysis. Mitochondria, which are plentiful in neurons and muscle fibers, play an important role in neuromuscular junction transmission. Therefore, impairments in both mitochondria and neuromuscular junction may be one of the key pathophysiological mechanisms leading to sarcopenia. Moreover, this article explores the structural and functional alterations in the neuromuscular junction and mitochondria in sarcopenia, suggesting that a deeper understanding of these changes could provide valuable insights for the prevention or treatment of sarcopenia.